Organized crime in cyberspace: How traditional organized criminal groups exploit the online peer-to-peer lending market in China - Wang, Peng (The British journal of criminology, 2021)
How do traditional organized criminal groups run their offline businesses on the internet? Drawing on interview data, news reports and interactions with illegal moneylenders, this article examines how loan sharks use the online peer-to-peer lending market to lend money to Chinese students at exorbitant interest rates. Illegal lenders employ techniques of deception, the sharing of compromising information (e.g. social contacts and nude photos) and professional legal services to develop internet-based loan scams to trap student borrowers. To enforce loan repayment, lenders have developed a new strategy: relational repression, which is the use of cyberviolence and the threat of revealing damaging information to clients’ social contacts. This puts enormous pressure on clients and their families to make payments. The use of relational repression reduces the need to resort to physical violence and bribe police officers.